(untitled) (Baghdad Science Journal, 2025)
A study of the singlet and triplet states of two electron systems in the first excited state was performed using a simple quantum mechanical model, which assigns the 1s,and 2s orbital with two different variational parameters. Our results agree with a high level calculation used by Snow and Bills.